2017
DOI: 10.1007/s12079-017-0407-5
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression of α1-antitrypsin Portland in MDA-MB-231 cells increased MT1-MMP and MMP-9 levels, but reduced tumour progression.

Abstract: The membrane bound matrix metalloproteinase MT1-MMP plays roles in modulating cell movement, independent of its abilities to remodel the extracellular matrix. Unlike many MMPs, MT1-MMP is activated in the Golgi prior to secretion by a pro-protein convertase, primarily furin. Regulation of the activation of pro-MT1-MMP has been methodically investigated, as altering the level of the active protein has broad implications in both activating other pro-MMPs, including pro-MMP-2, and many subsequent remodelling even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
5
2
Order By: Relevance
“…TGF-β1 is deemed to be processed by the subtilisin-like proprotein convertase, Furin 5 . In this study, we found that exogenous TGF-β1 could induce Furin expression at both the mRNA and protein levels ( Supplementary Fig.…”
Section: Mecp2 Regulates the Expression Of Furin To Activate Tgf-β1mentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β1 is deemed to be processed by the subtilisin-like proprotein convertase, Furin 5 . In this study, we found that exogenous TGF-β1 could induce Furin expression at both the mRNA and protein levels ( Supplementary Fig.…”
Section: Mecp2 Regulates the Expression Of Furin To Activate Tgf-β1mentioning
confidence: 99%
“…Meanwhile, it is generally accepted that the activation of TGF-β1/Smad signaling is critical to induce EMT 3 , 4 . Furin has been reported to promote the migration and invasion abilities of human cancer cells via pro-MT1-MMP and/or pro-TGF-β1 activation 5 , 6 . Furin is a member of the family of subtilisin/kexin-like proprotein convertases (PCs), which contribute to the activation of precursor pro-proteins to become biologically active 7 .…”
Section: Introductionmentioning
confidence: 99%
“…It would be of interest to further investigate whether single or co‐expression of the top 3 genes as identified in the patient group experiencing VTE before colorectal cancer diagnosis ( REG4 , SPINK4 , and SERPINA1 ) could serve as a strong predictor of VTE in colorectal cancer patients. Additionally, these three genes encode secretable proteins and therefore future work is required to study if plasma levels could also serve as prognostic biomarkers 58, 59, 60. Furthermore, it would be interesting to investigate if there is a relationship and/or synergism with mutational status of K‐ras, as this is already associated with CAT in colorectal cancer 43.…”
Section: Unbiased Screen For Risk Factors In Catmentioning
confidence: 99%
“…Additionally, these three genes encode secretable proteins and therefore future work is required to study if plasma levels could also serve as prognostic biomarkers. [58][59][60] Furthermore, it would be interesting to investigate if there is a relationship and/or synergism with mutational status of K-ras, as this is already associated with CAT in colorectal cancer. 43 Finally, future work may demonstrate that there is a link between the expression profiles in CAT and different subtypes of colon cancer, 61 Overexpression of Reg4 is associated with tumor progression, metastasis and reduced survival.…”
Section: Unbiased Screen For Risk Factors In Catmentioning
confidence: 99%
“…Treatment with the broad spectrum MMP inhibitor BB94 increased MT1-MMP expression, but decreased MMP-2 activation and did not alter pERK protein levels [11]. In mammalian MDA-MB-231 cells, inhibition of pro-MT1-MMP activation elevated global MT1-MMP and pERK levels, but decreased MMP-2 levels [12]. These mammalian cell studies demonstrated that when MT1-MMP levels are altered, pERK and MMP-2 activation levels alter in different ways depending on treatment.…”
Section: Introductionmentioning
confidence: 99%